Accounting for decarbonisation and reducing capital at risk in the S&P500. Issue 1 (March 2018) - Haslam, Colin; Tsitsianis, Nick; Lehman, Glen; Andersson, Tord; Malamatenios, John
Highlights: Carbon emissions in the S&P500 for the period 2008 to 2014 have not been reduced. Carbon intensive business models present a threat to financial stability from 'stranded assets' and 'carbon bubbles'. Financial institutions should migrate investment portfolios away from carbon intensive business models. Carbon intensive business models are conjoined to less carbon intensive business models which generate substantial financial leverage. Abstract: This article accounts for carbon emissions in the S&P 500 and explores the extent to which capital is at risk from decarbonising value chains. At a global level it is proving difficult to decouple carbon emissions from GDP growth. Top-down legal and regulatory arrangements envisaged by the Kyoto Protocol are practically redundant given inconsistent political commitment to mitigating global climate change and promoting sustainability. The United Nations Environment Programme (UNEP) and European Commission (EC) are promoting the role of financial markets and financial institutions as drivers of behavioural change mobilising capital allocations to decarbonise corporate activity.